Differentiation of hemoglobin in the black population of Lima - Aste Salazar, Humberto (1957)
Within our roadmap in this area, given that it is in blacks more often where most of the known abnormal hemoglobins are noted, consider it appropriate to study differentiation of hemoglobins in hospital black population of Lima, reason this preliminary note.